Organogénesis in vitroen Dalbergia retusa (Papilonaceae) - Valverde Cerdas, Lisette (2004)
Plants were obtained via organogenesis from hypocotyl explants of Dalbergia retusafrom in vitrogerminated seedlings. Adventitious bud induction was achieved on Murashige and Skoog medium containingfive BA (benzyladenine) concentrations. The best BA concentration for budding induction and budding devel-opment was 8.8μ M. Shoot rooting was obtained on half-strength modified MS basal medium, supplementedwith 20g.l-1of sucrose and five concentrations of indole-3-butyric acid (IBA). The highest number of shoot root-ing was obtained with 19.7μ M IBA but the highest average number of roots for plantlet was achieved with24.6μ M IBA. Plants were transferred to greenhouse conditions